Cryopreservation of boar semen in 0.5mL straws at low spermatozoa concentration is better than high concentration to maintain sperm viability - Ravagnani, Gisele M.; Torres, Mariana A.; Leal, Diego F.; Martins, Simone M. M. K.; Papa, Frederico O. [UNESP]; Dell'Aqua Junior, Jose A. [UNESP]; Alvarenga, Marco A. [UNESP]; Andrade, Andre F. C. (Revista Pesquisa Veterinaria Brasileira, 2018)
To date, no studies have been performed evaluating the effect of boar spermatozoa concentration in 0.5mL freezing straws, leading us to examine this question. Each sperm-rich fraction of the ejaculate (n=25) was diluted at five different sperm concentrations (100, 200, 300, 600 and 800 x 10(6) spermatozoa/mL), packaged in 0.5mL straws, and subsequently frozen. After thawing, the sperm from all of treatment groups were analyzed to determine motility characteristics using a sperm class analyzer (SCA-CASA), and their plasma and acrosomal membrane integrity, mitochondria! membrane potential, sperm membrane lipid peroxidation and fluidity were analyzed by flow cytometry. An increase in spermatozoa concentration above 300x10(6) spermatozoa/mL in a 0.5mL straw impaired (p<0.05) the total and progressive motility, curvilinear velocity, straight-line velocity, linearity and beat cross frequency. However, the plasma and acrosomal membrane integrity, mitochondria] membrane potential, membrane lipid peroxidation and fluidity were not influenced (p>0.05) by high spermatozoa concentrations at freezing. Therefore, to increase spermatozoa survival and total and progressive motility after thawing, boar spermatozoa should be frozen at concentrations up to 300x10(6) spermatozoa/mL.
Keywords: Cryopreservation; boar semen; spermatozoa concentration; sperm viability; cryoinjury; cryocapacitation; swine